Outside in the gardens and houses of Tichenor & Thorp - Tichenor, M. Brian; Nasatir, Judith; Thorp, Raun (New York Vendome Press, 2017)
"Tichenor & Thorp design exceptional properties that integrate large-scale residences and luxurious gardens and landscapes into a singular, unified vision. Deeply fluent in historical architectural styles and the modern California tradition, the duo's projects resonate with individuality and precedent. Featured here are a Spanish-inflected courtyard house and garden in Las Palmas; a Bel Air estate tinged with English and French influences; a Newport Beach hilltop hideaway that evokes a Portuguese quinta; a Pasadena retreat inflected with John Soane-inspired details; two luxe Manhattan apartments; and a mountain getaway in Jackson Hole, Wyoming. Illustrated with specially commissioned photographs by Roger Davies and Brian Tichenor's own watercolors, drawings, and plans, and with a foreword by Pilar Viladas, Outside In shares "Hollywood's best-kept secret" with the world"--
2
Keywords: Tichenor & Thorp (Firm); ARCHITECTURE / Buildings / Residential; ARCHITECTURE / Interior Design / General; Architecture, Domestic -- Themes, motives; DESIGN / Interior Decorating; Gardens, American